Toleransi 20 Genotipe Tanaman Tomat terhadap Naungan - Baharuddin, Raisa; Chozin, M A; Syukur, Muhamad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTLow light intensity is a limiting factor in the intercropping system. The aim of this study was to evaluate the production and fruit quality of 20 tomato genotypes under shading condition. This study was conducted at Cikabayan experimental station-University Farm of IPB from January to April 2013. The research was arranged in a nested design with three replicates. The main plot was shading intensity consisted of four levels, i.e., 0, 25, 50, and 75%, while the sub plot was 20 genotypes of tomato. Results of this study showed that the number and weight of fruit per plant under 25% shade were increased for most of the tested genotypes, while under 50% shade showed a high diversity among genotypes. Based on relative production under 50% shade, genotypes can be grouped into four, i.e: sensitive, tolerant, moderate, and shade-ecotype-like genotypes. 50% shade significantly affected total soluble solids and total titrated acid, but did not significantly the firmness of fruit of shade-ecotype-like genotypes.Keywords: intercropping, production, shade, quality